Estimation of USLE crop and management factor values for crop rotation systems in China - Qian-kun GUO; Bao-yuan LIU; Yun XIE; Ying-na LIU; Shui-qing YIN (Journal of Integrative Agriculture)
Soil erosion on cropland is a major source of environmental problems in China ranging from the losses of a non-renewable resource and of nutrients at the source to contamination of downstream areas. Regional soil loss assessments using the Universal Soil Loss Equation (USLE) would supply a scientific basis for soil conservation planning. However, a lack of information on the cover and management (C) factor for cropland, one of the most important factors in the USLE, has limited accurate regional assessments in China due to the large number of crops grown and their complicated rotation systems. In this study, single crop soil loss ratios (SLRs) were collected and quantified for 10 primary crops from past studies or reports. The mean annual C values for 88 crop rotation systems in 12 cropping system regions were estimated based on the combined effects of single crop SLRs and the percentage of annual rainfall erosivity (R) during the corresponding periods for each system. The C values in different cropping system regions were compared and discussed. The results indicated that the SLRs of the 10 primary crops ranged from 0.15 to 0.74. The mean annual C value for all 88 crop rotation systems was 0.34, with a standard deviation of 0.12. The mean C values in the single, double and triple cropping zones were 0.37, 0.36 and 0.28, respectively, and the C value in the triple zone was significantly different from those in single and double zones. The C values of dryland crop systems exhibited significant differences in the single and triple cropping system regions but the differences in the double regions were not significant. This study is the first report of the C values of crop rotation systems in China at the national scale. It will provide necessary and practical parameters for accurately assessing regional soil losses from cropland to guide soil conservation plans and to optimize crop rotation systems.